2021
DOI: 10.1038/s41419-021-04317-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of necroptotic extracellular vesicles

Abstract: Necroptosis is a regulated and inflammatory form of cell death. We, and others, have previously reported that necroptotic cells release extracellular vesicles (EVs). We have found that necroptotic EVs are loaded with proteins, including the phosphorylated form of the key necroptosis-executing factor, mixed lineage kinase domain-like kinase (MLKL). However, neither the exact protein composition, nor the impact, of necroptotic EVs have been delineated. To characterize their content, EVs from necroptotic and untr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 57 publications
2
38
1
Order By: Relevance
“…Both EM and NTA showed that SEVs-isolated by two different methods-have similar size distributions regardless of their RIPK3 genotypes or whether they were undergoing necroptosis. NEEs appear to share about half the proteins (1023) identified in similar NEEs in macrophages (Shlomovitz et al, 2021) although RIPK3 was uniquely identified in our study (Table S5).…”
Section:  Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Both EM and NTA showed that SEVs-isolated by two different methods-have similar size distributions regardless of their RIPK3 genotypes or whether they were undergoing necroptosis. NEEs appear to share about half the proteins (1023) identified in similar NEEs in macrophages (Shlomovitz et al, 2021) although RIPK3 was uniquely identified in our study (Table S5).…”
Section:  Discussionmentioning
confidence: 75%
“…Close examinations of our proteomic data revealed the presence of several Rab-family members in SEVs including Rab21, Rab6a, Rab6b, Rab18 and others Rab11a and Rab11b. Rab11 isoforms-Rab11a, Rab11b, and Rab25-have previously been found in SEVs including those secreted by necroptotic cells (Shlomovitz et al, 2021). To address whether RIPK3 and Rab11 could be mechanistically involved in SEV release during necroptosis, we immunoprecipitated extract from WCL and NEEs with an anti-RIPK3 antibody and subjected the resulting complexes to mass-spectrometry analysis.…”
Section:  Rabb Interacts With Ripk Within Neesmentioning
confidence: 99%
“…There is a large body of evidence that EVs generated by either non-inflammatory or inflammatory types of cell death have discordant effects upon uptake by phagocytic cells. Recently, it was shown that uptake of necroptotic cell-derived EVs by macrophages results in the secretion of pro-inflammatory cytokines (tumour necrosis factor (TNF) and CCL2) 26 . Inflammasome activation during pyroptosis induces a marked release of exosomes, and a connection has been established between inflammasome-mediated cleavage of Rab-interacting lysosomal protein (RILP) and the selective loading of microRNAs (miRNAs) into EVs 27 .…”
Section: Innate Immunity and Inflammationmentioning
confidence: 99%
“…Oligomerized MLKL has the ability to bind directly to lipids, allowing polymerized MLKL to form membrane permeable pores, disrupt cell membrane integrity, and undergo necroptosis ( 71 , 85 ). However, it inhibits the formation of complex iib to inhibit necroptosis, so the role of RIPK1 in cells can be determined by targeting the drug to determine whether the cells survive or undergo necroptosis ( 74 , 86 , 87 ).…”
Section: Necroptosismentioning
confidence: 99%